(MIS)Allocation Effects of an Overpaid Public Sector. Issue 2 (3rd September 2020) - Cavalcanti, Tiago; Santos, Marcelo
Abstract: There is a large body of evidence showing that for many countries the structure of wages and pensions and the labor law legislation are different for public and private employees. Such differences affect the occupational choice of agents and might generate some type of misallocation. We develop a life-cycle model with endogenous occupational choice and heterogeneous agents to study the implications of an overpaid public sector. The model is estimated to be consistent with micro and macro evidence for Brazil, a country with a high public sector earnings premium. Our counterfactual exercises demonstrate that public–private earnings premium can generate important allocation effects and sizeable productivity losses. For instance, a reform that would decrease the public–private wage premium from its benchmark value of 19% to 15% and would align the pension of public sector workers with the one in place for private sector workers could increase aggregate output by nearly 11.2% in the long run without any decrease in the supply of public infrastructure. We provide a decomposition of the aggregate effect into changes in factors accumulation and changes in TFP and implement a welfare distributive analysis.